HUBUNGAN ANTARA FAKTOR-FAKTOR EKSTRINSIK PENYEBAB KARIES DENGAN INDEKS DMF-T - Dhea Sarahtika Siagian; Denden Ridwan Chaerudin; Megananda Hiranya Putri; Nurul Fatikhah (Poltekkes Kemenkes Bandung, 2026)
Dental caries remains dominant oral health problem. The Decay, Missing and Filling Teeth (DMF-T) Index is used to measure cumulative caries experience. This study aims to analyze the relationship between extrinsic factors (education level, knowledge, motivation, and behavior) and the DMF-T Index. This type of research is analytical research with a cross-sectional design. The population in this study were all patients who visited the First Dental Clinic of the Ministry of Defense in Jakarta in October 2025. Data collection was carried out through an accidental sampling scheme with a sample size of 106 respondents calculated using the Lemeshow formula and anticipated dropout. The instruments used were questionnaires on factors of education level, knowledge, motivation, behavior, and the DMF-T index examination. Fisher's Exact Test was used for data analysis with a significance threshold of α=0.05. Referring to the caries level classification standard, the majority of subjects in this study were in the high DMF-T Index category, with percentage reaching 70.8% (75 respondents). A total of 84 respondents (79.2%) were at a higher education level, 86 respondents (81.1%) had good knowledge, 101 respondent (95.3%) had high motivation, and respondents who had moderate behavior were 59 respondents (55.7%). The results of statistical tests showed no relationship between the factors of Education Level, Knowledge and Motivation with the DMF-T index at the research location (p>0.05). However, the behavioral variable and the DMF-T index were related (p=0.032). According to this study, the only extrinsic factor that significantly influenced the DMF-T Index was the behavioral factor.